A characterization of singular Schrödinger operators on the half-line. Issue 4 (7th December 2021) - Scandone, Raffaele; Luperi Baglini, Lorenzo; Simonov, Kyrylo
Abstract: We study a class of delta-like perturbations of the Laplacian on the half-line, characterized by Robin boundary conditions at the origin. Using the formalism of nonstandard analysis, we derive a simple connection with a suitable family of Schrödinger operators with potentials of very large (infinite) magnitude and very short (infinitesimal) range. As a consequence, we also derive a similar result for point interactions in the Euclidean space R^3, in the case of radial potentials. Moreover, we discuss explicitly our results in the case of potentials that are linear in a neighborhood of the origin.